Associations between prepartum urine pH and periparturient blood calcium concentrations in multiparous Holstein cows - Goff, Jesse P.; Melendez, Pedro; Bartolome, Julian A.; Overton, Thomas R.; Leno, Brittany M.; Graef, Geneva; Drackley, James K.; Glosson, Kristen M.; Zhang, Xiangfei; LeBlanc, Stephen J.; Couto-Serrenho, Rita; Santos, José E. P.; et al. (Frontiers in Veterinary Science, 2025)
IntroductionMetabolic alkalosis induced by prepartum diet cations impairs Ca homeostasis in the periparturient cow. Adding anions to prepartum diets reduces blood pH improving periparturient Ca homeostasis. Urine pH generally reflects blood pH and is practical to measure on farm. The degree to which urine should be acidified to increase periparturient blood Ca concentration is not well defined.Materials and methodsPrepartum urine pH and periparturient blood Ca concentrations determined in 660 multiparous Holstein cows from 9 studies were analyzed. Least Square Means of the lowest blood Ca concentration (Ca nadir) observed in cows within 6 urine pH categories (≤ 5.75, 5.76 to 6.25, 6.26 to 6.75, 6.76 to 7.25, 7.26 to 7.75, and ≥ 7.76) were determined. Data were analyzed across all 660 cows and then by parity.ResultsAcross all cows, the Ca nadir was lowest and the incidence of cows with Ca nadir < 2.00 mM, indicative of subclinical hypocalcemia (SCH), was greatest when urine pH was ≥ 7.76. Mean Ca nadir increased in all cows with urine pH < 7.75. There was no significant difference in Ca nadir or % of cows with SCH when prepartum urine pH was < 7.75. This was also the case for 2nd and 3rd parity cows. However, in ≥ 4th parity cows, those with urine pH between 6.26 and 6.75 had significantly higher Ca nadir than cows with urine pH above 7.25 or below 5.75. Calcium nadir and blood Ca concentrations at 2 days in milk (DIM) were highly correlated (r = + 0.58), and blood Ca concentrations at 2 and 4 DIM were moderately correlated (r = + 0.43). Blood Ca concentration at 4 DIM was weakly associated with Ca nadir (r = + 0.30).DiscussionThese analyses support acidification of cows to achieve prepartum urine pH below 7.75 to increase blood Ca nadir for 2nd and 3rd parity cows. For ≥ 4th parity cows, the highest blood Ca nadir was observed with urine pH below 7.25 and above 5.75. For ≥ 4th parity cows, urine pH below 5.75 was associated with significantly lower blood Ca nadir.